(untitled) (Marketing Journal, 2025)
The article examines the main trends in international trade in circular goods produced within the framework of the “green” economy and analyzes the opportunities and risks associated with trade in circular goods. Incorrect identification of goods, gaps in the Harmonized System (HS), contradictions between HS and the provisions of the Basel Convention in relation to waste trade are identified as the main problems in the trade of these goods.